Conjugated Polymer/Nanocrystal Nanocomposites for Renewable Energy Applications in Photovoltaics and Photocatalysis - Su, Yu-Wei; Lin, Wei-Hao; Hsu, Yung-Jung; Wei, Kung-Hwa (My University, 2014)
Conjugated polymer/nanocrystal composites have attracted much attention for use in renewable energy applications because of their versatile and synergistic optical and electronic properties. Upon absorbing photons, charge separation occurs in the nanocrystals, generating electrons and holes for photocurrent flow or reduction/oxidation (redox) reactions under proper conditions. Incorporating these nanocrystals into conjugated polymers can complement the visible light absorption range of the polymers for photovoltaics applications or allow the polymers to sensitize or immobilize the nanocrystals for photocatalysis. Here, the current developments of conjugated polymer/nanocrystal nanocomposites for bulk heterojunction-type photovoltaics incorporating Cd- and Pb-based nanocrystals or quantum dots are reviewed. The effects of manipulating the organic ligands and the concentration of the nanocrystal precursor, critical factors that affect the shape and aggregation of the nanocrystals, are also discussed. In the conclusion, the mechanisms through which conjugated polymers can sensitize semiconductor nanocrystals (TiO2, ZnO) to ensure efficient charge separation, as well as how they can support immobilized nanocrystals for use in photocatalysis, are addressed.
Keywords: conjugated polymers; nanocrystals; quantum dots; photovoltaics; photocatalysis